PERFORMANCE OF QUAIL BIRD 0 – 4 WEEKS THAT GIVEN A TUMERIC (Curcuma domestica Val.) SOLUTION IN DRINKING WATER - N. M. T, Padmini; Dewi, G. A. M. K.; Candrawati, D. P. M. A. (Jurnal Peternakan Tropika; Vol 9 No 3 (2021): Vol. 9 No. 3 Tahun 2021; September - December, 2021)
This experiment was conducted to find out performance  quail was given turmeric (Curcuma domestica Val. ) solution on drinking water for 4 weeks. The design of experimet is Completely Randomized Design (CRD) consisting of 3 treatments and 6 replications. The turmeric solution  treatment are A : without turmeric solution, B ; 1% turmeric solution, and C : 2% turmeric solution. The turmeric used in this study is turmeric rhizome. The observed variables are intial body weight, final body weight, body weight gain, feed consumption, drinking water consumption, dan feed conversion ratio (FCR). The results indicated was given 1% - 2% turmeric (B and C) on drinking water can increased feed consumption 6,35% - 16,78% compared with treatment A (without turmeric), but the treatment without turmeric 1%, and 2% (A, B, and C) has not been able to increased the water consumption, final body weight, body weight gain, and decreased feed conversion ratio (FCR) value.  Based on the result  of the reseach, it can be concluded that quail was given turmeric solution (Curcuma domestica Val. ) 1% and 2% on drinking water can increased feed consumption, but not able increased water consumption, final body weight, body weight gain, and decreased feed conversion ratio (FCR) value.   Keywords : quail, turmeric solution, performance